Creating Special Educational Environments for Students with Visual Impairments at the Moscow State University of Psychology and Education: Practical Outcomes - Kuravsky L. S.; Vasina L.G; Sokolov V.V (Moscow State University of Psychology and Education, 2018)
The paper describes practical outcomes of implementing a model of special educational settings for students with visual impairments enrolled in bachelor's programmes in Mathematical Support and Administration of Information Systems and Applied Computer Science. These outcomes suggest that project-based learning, special educational settings, active involvement in research and participation in finding solutions to relevant practical tasks promotes high quality training in students with disabilities.